A Comparative Study on Duration of Supraclavicular Plexus Block Using Dexamethasone vs Tramadol as an Adjuvant to Bupivacaine for Arm and Forearm Surgeries - Sultan, Najam; Javed, Hafiz Muhammad; Mir, Ahmed Jahangir; Adnan, Hafiz; Ahmed, Daud (Biological and Clinical Sciences Research Journal, 2025)
Supraclavicular brachial plexus block is widely used for upper limb surgeries due to its rapid onset and reliable anesthesia. However, the limited duration of analgesia with local anesthetics necessitates the use of adjuvants. Dexamethasone and tramadol are commonly used agents, but comparative evidence in the Pakistani population remains limited. Objective: To compare the effects of dexamethasone versus tramadol as adjuvants to bupivacaine on the duration of supraclavicular brachial plexus block in patients undergoing arm and forearm surgeries. Methods: This comparative study was conducted at the Department of Anesthesia, Aziz Bhatti Shaheed Teaching Hospital, Gujrat, from April 2024 to March 2025. A total of 70 patients (ASA I–II), aged 18–60 years, were assigned to two groups. Group A received bupivacaine with dexamethasone (8 mg), while Group B received bupivacaine with tramadol (100 mg). Primary outcomes included onset and duration of sensory and motor block, and duration of analgesia. Secondary outcomes included pain scores (VAS), rescue analgesic requirement, and adverse effects. Data were analyzed using SPSS version 26, with p ≤ 0.05 considered statistically significant. Results: The mean age of participants was 38.9 ± 11.6 years, with a predominance of males. Baseline characteristics were comparable between groups. Dexamethasone demonstrated significantly faster onset of sensory (11.2 ± 2.4 vs 13.1 ± 2.8 minutes, p=0.003) and motor block (15.6 ± 3.1 vs 17.9 ± 3.5 minutes, p=0.005). It also significantly prolonged sensory block (812.4 ± 108.6 vs 641.8 ± 96.3 minutes), motor block (694.2 ± 101.7 vs 548.9 ± 88.4 minutes), and duration of analgesia (928.6 ± 121.4 vs 716.5 ± 104.9 minutes) (p<0.001 for all). Pain scores were significantly lower in the dexamethasone group at 6, 12, and 24 hours. Fewer patients required early rescue analgesia (22.9% vs 60.0%, p=0.002), and total analgesic consumption was reduced. Hemodynamic parameters were comparable, while nausea and vomiting were more frequent in the tramadol group. Conclusion: Dexamethasone is superior to tramadol as an adjuvant to bupivacaine in supraclavicular brachial plexus block, providing faster onset, prolonged analgesia, improved pain control, and fewer adverse effects.